Opportunistic intracellular bacteria and immunity - Paradise, Lois J.; Friedman, Herman; Bendinelli, Mauro (Kluwer Academic Publishers, 2002)
Immune Defenses against Intracellular Bacterial Infections -- Genetic Regulation of Host Responses to Salmonella typhimurium -- Host Resistance and Mycobacterium tuberculosis Infection -- The Influence of Adrenal Steroids on Macrophage and T-cell Function in Tuberculosis -- Mycobacterium leprae as an Opportunistic Pathogen -- Immunology and Immunopathology of Mycobacterial Infections -- Mycobacterium avium-Complex Infections and Immunodeficiency -- Pathogenesis of Legionella pneumophila Infection -- Immune Responses to Legionella -- The Infectious/Pathogenic Processes Driven by Listeria monocytogenes in Laboratory Mice -- Rhodococcus equi: Pathogenesis and Replication in Macrophages -- Bartonella Infections in the Immunocompromised Host -- Chlamydia trachomatis Infections -- Chlamydia Infection and Pneumonia -- Brucella Infections and Immunity -- Antibiotic Treatment of Infections with Intracellular Bacteria.